(untitled) (London Journal of Research In Management & Business, 2025)
The oil and gas sector play a crucial role in global economic development, yet it faces increasing scrutiny due to its environmental impact. In Nigeria, Africa’s largest oil producer, the sector significantly contributes to environmental degradation, including oil spills and gas flaring. This study explores the effect of green accounting on the market value of listed oil and gas companies in Nigeria. Specifically, it aims to assess the impact of environmental expenditure disclosure (EEXD) and stakeholder engagement disclosure (SED) on the market value of these companies. The population of the study comprises nine (9) publicly listed oil and gas companies on the Nigerian Exchange Group (NGX) as of December 31, 2023. Using a purposive sampling technique, five (5) companies with substantial environmental disclosures in their annual reports were selected. Data were sourced from the NGX Fact Book and the annual reports of the selected companies from 20142023. Descriptive statistics were employed to summarise the data characteristics, while correlation analysis examined the relationships between environmental expenditure disclosures and market value. Multivariate regression analysis was conducted to assess how EEXD and SED predict market value, with statistical analysis performed using Jamovi software (Version 2.3.28). The findings reveal that both Environmental Expenditure Disclosure and Stakeholder Engagement Disclosure have positive and statistically significant effects on market value. This study contributes to the growing body of literature on environmental disclosures in Nigeria’s oil and gas sector, emphasising the importance of transparent disclosure practices to foster market competitiveness and stakeholder confidence.